Using an anti-racist research framework to design studies of oral human papillomavirus and oropharyngeal cancer in San Francisco: rationale and protocol for the Health Equity and Oral Health in People living with HIV (HEOHP) qualitative study - Alessandro Villa; Alexandra L Hernandez; Elena O Lingas; William Juarez; Joel Palefsky (BMJ Open)
Introduction The goal of our research programme is to develop culturally appropriate patient-specific interventions for primary and secondary prevention of human papillomavirus (HPV)-related oropharyngeal cancer (OPC) among people living with HIV (PLWH); PLWH are at a higher risk for OPC than the general population and, as with many cancers, there are disparities in OPC health outcomes by race and ethnicity. Our study incorporates an anti-racist research framework that proposes considering racism as a foundational sociocultural system that causes ill health. We expand the framework to include biases due to gender, sexual orientation, HIV status and membership in other non-dominant groups. Our research programme focuses on HPV-related OPC among people living with PLWH, and on how intersecting identities may impact an individual’s experience with oral health, obtaining regular and appropriate oral healthcare, knowledge and perceptions of oral HPV infection, risk factors for OPC and HPV vaccination.Methods and analysis We will follow a grounded theory (GT) qualitative research methodology using focus group discussions (FGDs) to collect data. We will invite PLWH with intersecting identities to participate in one of 12–18 FGDs with 5–8 participants per group. Focus groups will be formed based on self-reported domains, including race, ethnicity, gender identity, sexual orientation and other identities that could impact oral health, such as smoking status, experience with homelessness or experience with drug use disorders. We do not know which aspects of intersecting identities are most salient to accessing oral healthcare. Using FGDs will allow us to gain this knowledge in a setting where participants can build on and reinforce shared understandings about oral healthcare. Following our GT methodology, analysis will occur concurrently with data collection, and emerging concepts or theories may result in changes to focus group guide questions. Initial focus group questions will be organised around our main objectives: (1) to identify individual, interpersonal and structural health equity factors that serve as barriers or facilitators to oral health status and care; (2) to explore knowledge and perceptions about causes, risk factors, prevention and screening for oral or OPC and (3) to elicit recommendations for improving access to regular and appropriate oral healthcare and suggestions on engaging PLWH from diverse identity groups in prevention interventions.Ethics and dissemination All methods and procedures were approved by the University of California, San Francisco, Institutional Review Board (approval number: 23-39307) and are in accordance with the Declaration of Helsinki of 1975, as revised in 2000. Participants are required to provide informed consent. The results of this study will be presented at scholarly meetings and published in peer-reviewed journals. In addition, a lay summary of results will be created and distributed to our participants and community through our website and social media.Trial registration number NCT06055868.